THE RELATIONSHIP BETWEEN KNOWLEDGE ABOUT ELDERLY GYMNASTICS AND THE INCIDENCE OF HYPERTENSION IN THE ELDERLY AT THE LEMAHDUHUR VILLAGE HEALTH CENTER, TEMPURAN DISTRICT, KARAWANG REGENCY IN 2022: HUBUNGAN PENGETAHUAN TENTANG SENAM LANSIA DENGAN KEJADIAN HIPERTENSI LANSIA DI PUSKESMAS LEMAHDUHUR DESA LEMAHDUHUR KECAMATAN TEMPPURAN KABUPATEN KARAWANG TAHUN 2022 - Sri Wulandari; Lina Indrawati; Kiki Deniati (Borneo Nursing Journal (BNJ), 2023)
Background: Elderly is a time when a person reaches maturity in cell size and function to cause setbacks over time. One of the health problems caused by a decrease in body functions due to the aging process is the cardiovascular system. Reduced strength of the heart muscle, arterosclerosis of the blood vessels and decreased ability to pump the heart because it works more so that hypertension occurs.The purpose of this study was to identify the relationship between elderly gymnastics knowledge and the incidence of hypertension in the elderly at the Lemahduhur Village health center, Tempuran District, Karawang Regency. Method:This research uses a quantitative type of research using a cross-sectional design. The population in this study was all elderly in the working area of the Weak Village Health Center, Tempuran District, Karawang Regency. Sampling in this study used a non-probability sampling technique through a purposive sampling approach so that a sample of 134 people was obtained. This study used a chi square test with a degree of meaning of α <0.05 to determine the relationship between elderly gymnastics knowledge and the incidence of hypertension in the elderly at the Lemahduhur Village health center, Tempuran District, Karawang Regency. Research Results: The results of statistical tests between elderly people who have good knowledge and experience hypertension are 86 people (64.2%), and elderly people who are moderately knowledgeable and have hypertension are 14 people (10.4%). The results of the study were significant where the P-value (0.021) <0.05 showed that there was a relationship between poor knowledge and the incidence of hypertension in the elderly. Conclusion: there is a relationship between poor knowledge and the incidence of hypertension in the elderly at the Lemahduhur Village health center, Tempuran District, Karawang Regency